Recycling of Red Mud as a Building Material via a Stabilization/Solidification Method - Yildiz, Aylin; Akyildiz, Aylin; Tinmaz Kose, Esra (Asian Journal of Chemistry, 2012)
This study examines stabilization/solidification techniques for red mud/cement systems that involve the production of construction products while minimizing contamination and recycling the red mud. In these techniques, the polluted components of red mud are fixed in a cement body via adsorption and confinement mechanisms and thus, the possible impact of these pollutants on the environment is minimized. In the first step of this study, the physical, chemical, radioactive and mineralogical properties of the material used were determined. Second, red mud was used to replace portland cement in the following proportions: 0, 5, 10, 15, 20, 25, 30, 40 and 50 % of portland cement by weight. Finally, the usability of red mud as a construction product and the environmental effects of such usage were determined.